The EFS Program to Enhance Students' Speaking Skills For Daily Conversation : (Study Case at MAN 1 Bandar Lampung) - Ma'rifatul Halimatus Sa’diyah; Desi Purpitasari (English Language and Education Spectrum, 2023)
This study aims to investigate implementing the "English for School" program at M.A.N. 1 Bandar Lampung. The method used in this research washe descriptive qualitative method. The data source was students, tutors, and teachers in M.A.N. 1, the Bandarlampung academic year 2022/2023, through direct observation, interviews, and documentation of learning outcomes. The discussion and the observation aimed to gather information from the students, English teachers, and English tutors. The consultation with teachers, tutors, and students shows that the "English for School" program is well used to improve students' speaking skills, including the vocabulary and expressions related to daily conversation. Besides, the observation result found that student's confidence in speaking skills improved because of more practicing in English Area, especially with the tutors, and presenting something in English in front of the class during the program. The program could motivate and stimulate the students to use English in daily activities with anyone, anywhere.